Influence of Air Spring Failure on Operation Safetyfor Straddle-type Monorail Vehicle - Du Zixue; Cao Danting (机车电传动)
The air spring rubber capsule rupture of straddle-type monorail vehicle model was established, and the safety performanceof vehicle system with air spring failure was analyzed, focusing on the overturning stability coefficient and horizontal wheel’s radialforce and rolling angle. The analysis result showed that vehicle driving safety became worse with failure of air spring, and guide wheelsappeared derailment phenomenon, affecting the safety of vehicle; In addition, when the vehicle speed reached 43 km/h, the stability of thevehicle with different air spring failure condition became poor, and it was necessary to reduce the speed of the vehicle.